Creation and analysis of additive-manufactured CT-equivalent phantom tissue surrogates (Transactions on Additive Manufacturing Meets Medicine, 2024)
Fused Deposition Modeling (FDM) can produce durable and cost-effective anatomical phantoms that meet specific X-ray contrast requirements. This study investigates the impact of infill patterns and densities on computed tomography (CT) numbers. Sixteen samples were created using various filaments, infill patterns, and densities. Infill densities ranged from 30% to 90% for cubic infill and from 80% to 100% for line infill. The samples were scanned with a clinical CT scanner and average Hounsfield Units (HU) and standard deviations were measured using regions of interest (ROI) on transversal CT images. The findings indicate that small variations in infill can significantly alter HU values, suggesting extensive applications for different phantom tissue types in X-ray imaging. Cubic infill is particularly suitable for lower HU values, such as those representing lung tissue, whereas line infill at different densities can produce HU values suitable for soft tissue applications, from adipose to liver.
Keywords: 3D-printed phantom; infill percentage; FDM; CT; Hounsfield Units